PERANCANGAN ANIMASI 2D FIKSI GUNA MEMPELAJARI PENYAKIT SKIZOFRENIA DENGAN JUDUL SPLIT MIND - Jenifer; Napitupulu, Junika (Universitas Methodist Indonesia, 2021)
Indonesian people knowledge about mental disorders and awareness about the environment is still classified as low, negative, or stigmatized views about mental illnesses patients end up frequently treated in the wrong way. Even though a lot of information about mental illnesses like schizophrenia can be found on the internet in many forms like articles, pictures, videos, and animations. The animation is a connector between education and entertainment because it is presented in an interesting and easy-to-understand way. Therefore the author interested to design an animation Teaser about environmental awareness and schizophrenia in the title